Morphological mutants of upland cotton as source of boll weevil resistance - Neto, Francisco das Chagas Vidal; Silva, Fanuel Pereira da; Bleicher, Ervino; Melo, Francisco Ivaldo Oliveira (Pesquisa Agropecuaria Brasileira, 2005)
This work aimed to evaluate the effects of three morphological mutants of upland cotton lines (Gossypium hirsutm L. r. latifolium Hutch.), isolated or in combination in the same cotton genotype, as a source of resistance to boll weevil, Anthonomus grandis Boheman, 1843 (Coleoptera, Curculionidae). The experiment was carried out in the field, under natural infestation, with a completely randomized block design arranged in a factorial 2´3 plus an additional treatment, with four replications. In a multiple choice test, the character mutant frego bract presented the higher reduction on boll weevil oviposition damage (34.71%), in relation to the normal equivalent. The okra leaf reduced the boll weevil damage only when associated with frego bract (40%). The combination of the three mutant characters in the same plant presented the least square percent with oviposition damage (23.13%).